Early childhood teacher education on cultural competence - NAECTE, Urban Education Teacher Research Network (New York, NY Routledge, 2019)
"Early Childhood Teacher Education on Cultural Competence discusses how early childhood preservice teachers can explore and gain cultural competence, enabling them to support students and families from diverse backgrounds. The textbook opens by describing the role of the university in preparing culturally competent teachers and then explores historical perspectives of cultural competence. Chapters then move toward more practical perspectives of supporting families from racially diverse backgrounds, understanding diverse families, interprofessional education and collaboration, teacher resiliency, and social justice" --
Introduction: Developing a Vision of Social Justice / Frances O'Connell Rust and Amanda Branscombe -- Part I: Social Justice through the Lens of Teacher Education Programs -- A Social Justice Model for Improving Teacher Effectiveness / Regena Nelson, Moi Mooi Lew, and Yuqian Shen -- Becoming a Teacher and Keeping On: Another Look at Resilience in Teaching / Janese Daniels and Edyth J. Wheeler -- The Role of the Classroom Library: A Catalyst for Social Justice / Susan Catapano -- Part II: A Look at Early Childhood Teacher Educators Study of Their Courses -- Developing an Understanding of Diverse Families: Considerations for Preparing Teacher Candidates / Nicole Taylor -- The University's Role in Preparing Culturally Competent Teachers / Sarah E. Huisman -- Understanding Cultural Competence Through a Historical Lens / Andrea D. Lewis, Ph.D. -- Part III: Social Justice When Early Childhood Teachers Moving into the Life of the Communities -- Teaching & Reaching Refugee and New Immigrant Children and Their Families / Susan Catapano and Candace Thompson -- Supporting Father Engagement in Classrooms and Schools / Meredith Jones -- The Emerging Role of Interprofessional Education and Collaboration for Fostering Culturally Competent Family Engagement: Implications for Teacher Education / Elizabeth Anderson and Youjung Lee -- Teachers' Role in Children's Understanding of Gender Identity / Jamie Solomon.
Includes bibliographical references and index.
Keywords: Multicultural education -- Study and teaching (Early childhood); Culturally relevant pedagogy; Early childhood teachers -- Training of; Student teachers -- Training of